Employment in the neighborhoods of Barcelona: health effects of an active labor market program in Southern Europe. (13th December 2019) - González-Marín, Patricia; Puig-Barrachina, Vanessa; Bartoll, Xavier; Cortés-Franch, Imma; Malmusi, Davide; Clotet, Eva; Cardona, Africa; Artazcoz, Lucía; Borrell, Carme
ABSTRACT: Background: The aim of this study was to analyze the changes in self-perceived health status and mental health among participants in an active labour market policy (ALMP) of Barcelona, and to assess whether the results differed according to the participants' social characteristics and their program trajectories. Methods: A pre–post intervention study was designed, including unemployed people participating in a return-to-work ALMP in 13 deprived neighborhoods of Barcelona; using one survey upon entering the program (pre), and another 1 year later (post). We assessed the prevalence of poor self-perceived health status and poor mental health (Goldberg-12 questionnaire) in both periods of time. We fit five Poisson regression models using generalized estimating equations (GEE) to measure changes in self-perceived health and mental health between pre- and post-intervention. Results: About 696 individuals (48% women) participated in the study, mainly manual workers. In both sexes, mental health improved (prevalence ratio [PR]—comparing post- and pre-periods for women: 0.49, 95% confidence interval [CI]: 0.39–0.61 and men: PR: 0.41, 95% CI: 0.32–0.53), whereas self-perceived health status remained stable or worsened. Men who remained unemployed reported poorer self-perceived health status, while no such association was observed among women. Conclusions: This study shows a mental health improvement among male and female participants.